Tantangan Guru Sekolah Dasar dalam Memanfaatkan Kecerdasan Buatan Generatif untuk Pembuatan Media Pembelajaran Interaktif: Studi Literatur - Lydia Grasellia; Eka Rismaynarti Purba; Revandika Adrianta Tarigan; Ria Septya Ningsih; Rustina Hutagalung; Rahmilawati Ritonga (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
The development of Generative AI technology offers real opportunities for the development of interactive learning media in primary schools, yet its implementation remains hindered by various structural and pedagogical challenges. This study aims to map the key challenges faced by primary school teachers in utilizing Generative AI for the creation of interactive learning media. This study employs a Systematic Literature Review (SLR) method with the PRISMA selection protocol. A total of 12 articles meeting the inclusion criteria were extracted and analyzed using a thematic synthesis approach. The analysis identified six main challenge clusters: (1) low digital competence among teachers; (2) pedagogical difficulties in adapting AI-generated output to the characteristics of primary school students; (3) infrastructure and technology access gaps; (4) absence of regulation and ethical guidelines for AI use; (5) content validity and quality concerns; and (6) the threat of deskilling and excessive teacher dependency on technology. This study concludes that the effectiveness of Generative AI in learning cannot rely solely on infrastructure, but requires strengthening teachers' AI literacy and clear ethical policies at the institutional level. A shift in policy focus is needed toward critical AI literacy, teacher competence resilience, and the formulation of clear ethical guidelines at the institutional level.